Factors that influence customer loyalty in fast food restaurants / Nur Mary Farisha Muhamad Narawi and Nur Syafiqah Hadi Rusdi - Muhamad Narawi, Nur Mary Farisha; Hadi Rusdi, Nur Syafiqah (2018)
Purpose - This paper aims to determine the factors that influences customer loyalty in fast food restaurants and develop a research framework to explains the factors that influences customer loyalty in fast food restaurants. Design/methodology/approach - The study use quantitative method by using the responses from 383 customers who answered a survey questionnaire in fast food restaurants . The data analysis will be used are descriptive statistic (frequencies, percentages, mean, and standard deviation), Pearson Correlation and Multiple Regression Analysis. Findings - The results of the study shows that food quality has a significantly strong and positive relationship with customer loyalty while, physical environment has a moderate strong relationship with customer loyalty. There have a significant between all factors that been testified towards customer loyalty. Research limitations/implications - results from the research shows that food quality is the most influence factor toward customer loyalty meanwhile the price is the lowest factor that influence customer loyalty in fast food restaurant among the customer at Amanjaya Mall, Central Square and Village Mall. The sample involved for this study is only from two malls which are Amanjaya Mall, Central Square and Village Mall in Sungai Petani, Kedah . The result or finding of this study may differ if this study also conducted in many mall that located in different state around north region of Peninsular Malaysia.